Factors Influencing Thai Health Workers’ Attitudes toward Providing Health Services to Migrants - Wichaikhum, Orn-Anong; Abhicharttibutra, Kulwadee; Nantsupawat, Apiradee (Pacific Rim International Journal of Nursing Research, 2024)
Many migrants currently use local Thai healthcare services while living and working in Thailand. Health workers’ attitudes toward providing health services to migrants significantly influence the quality of their healthcare. This study aimed to describe and compare health workers’ attitudes toward providing health services to migrants between health professionals and supportive health workers and examine the personal and system factors that predict health workers’ attitudes towards health services. A cross-sectional design was applied in this study. A total of 1,356 health workers in Thailand were selected using multi-stage random sampling. The research instruments included the Migrants’ Cultures and Contexts Questionnaire and the Health Workers’ Attitudes toward Providing Health Services to Migrants Questionnaire. Data were analyzed using the Mann-Whitney U test and binary logistic regression. Most health professionals (91.05%) and supportive health workers (91.71%) had positive attitudes toward health services for migrants. The appropriateness of health workers’ numbers and knowledge about migrants’ cultures and contexts could mutually influence the health workers’ attitudes, accounting for only 3.6% of the variance. Reinforcing positive attitudes among health workers can be done by providing praise for good health services. However, further studies on the accessibility, quality of care services, cost, and migrants’ satisfaction are needed before appropriate intervention and policy can be improved.